Life Orientation and Personality Attributes: Implications on Posttraumatic Growth (PTG) Among Diagnosed Cancer Patients in Ibadan, Nigeria - Olaseni O., Abayomi; Ayodele O., Israel; F., Femi Agberotimi (International Journal For Research In Health Sciences And Nursing, 2016)
This study examined life orientation and personality attributes determining posttraumatic growth among cancer patients in Ibadan. One hundred and twenty (120) diagnosed cancer patients participated in the study. A structured questionnaire was used for data collection. Hypotheses were analyzed using hierarchical regression. Results showed that age, gender, education, and knowledge of diagnosis significantly predict posttraumatic growth (F (4, 115) = 2.64, p < 0.05, R2 = 0.14). Life orientation, neuroticism, and openness were significant in predicting posttraumatic growth controlling for socio-demographic factors (F (7, 112) = 3.80, p <.001, R2 = 0.90). In conclusion, individuals with terminal illness can still experience growth and psychological wellness despite their traumatic experiences if healthy dispositions such as optimism and emotional stability are developed in them. We recommend involvement of mental health practitioners especially clinical psychologists in the management of patients with traumatic experience in order to assist attain optimal wellbeing.